The crisis and the global economy: A shifting world order? - Razeen Sally (European Centre for International Political Economy (ECIPE), 2011)
The global economic crisis has sparked short-term divergence of economic performance between the West and emerging markets, and thereby accelerated the longer-run convergence of the latter on the former. This Shift to the East is also even more evident in international trade and FDI than it is in other channels of globalisation. But emerging markets' political and economic institutions, and intra-regional divisions, continue to hold back their rise. That means the Shift to the East will not translate into Chinese or other emerging-market leadership for a long time to come - if ever. The USA is still the fulcrum of international relations, and the world is far from being "post-American". Thus the economic shift to emerging markets, accelerated by the crisis, does not translate into a paradigmatic shift in global political-economic order. But it does insert more multipolarity and uncertainty into that order, and leaves more of a leadership vacuum. (...)
Keywords: 330; Wirtschaftskrise; Internationale Wirtschaftsbeziehungen; Welt